The Potential of Bioethanol as a Viable Alternative to Fossil Fuels - Rabiu, K. O.; Abidoye, L. K.; Oriaje, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Environmental challenges from fossil fuel emission have global issues and have contributed immensely to climate change. Bioethanol has experienced unprecedented level of attention due to its value as substitute to fossil fuel. Besides being a renewable and sustainable source of energy, it is also efficient, available and environmentally friendly. Global production of bioethanol continues to increase and will probably continue to dominate the alternative fuels market in the next decade. It is important to emphasize that for bioethanol to be a viable alternative, it must have ecological benefits, be economically competitive and its production must be in commercial scales without affecting the food production. This paper explains the problems and possible solutions in the production of bioethanol; since biofuel produces clean energy which can reduce the emission of CO2 into the atmosphere.